A clinico-epidemiological study of herpes genitalis in a tertiary care institution in Northern Kerala - Sreekanth, Sukumarakurup; Ambooken, Betsy; Sasidharanpillai, Sarita; Eranhikkal, Shibili (International Journal of Research in Dermatology, 2017)
Background: Herpes genitalis, has assumed greater importance, being the most common genital ulcer disease nowadays. Hence we aimed to study and analyse the epidemiology of herpes genitalis among STI clinic attendees of our institution during the three year study period. Methods: Previous case records of those who attended the STI clinic of our tertiary care institution with herpes genitalis from 2009 January to 2011 December were reviewed, data collected and studied. Results: 87 of the 530 patients (16.4%) who attended our STI clinic during the three year study period were diagnosed to have herpes genitalis. Females (57) outnumbered males (30) and majority of the affected belonged to the 20-39 age group (58/87, 66.7%). The common clinical types noted were primary herpes genitalis in females (38/57, 66.7%) and recurrent herpes genitalis (15/30, 50%) in males. Conclusions: The facts that all female patients except one were married, only 7.7 % of female patients had either EMC or PMC and many had developed symptoms within one year of their marriage, indicated that marital contact is the commonest cause of herpes genitalis in females in this locality. Significant percentage of primary herpes occurring in pregnant females points to the necessity of pre-marital counselling regarding various STIs and their respective modes of transmission. The study also indicated that males tend to get recurrences for a more prolonged period (2 months to 30 years) , compared to females ( 2 months to 5 years).